El trabajo infantil en una comunidad campesina de zona rural en Perú - Chachi Montes, Lizardo (2017)
The purpose of the research was to identify the types of activities carried out by children of the peasant community in rural areas. The methodology is descriptive, for this purpose, observation instruments, an interview guide for home visits and a survey questionnaire have been designed; the participants were 16 students between boys and girls from 1st to 6th grade and their parents. Parents and their minor children were surveyed by visiting their homes from 5 p.m. from now on, because they have more time for interviews than in the morning; likewise, an interview has been conducted with the school's teachers. Regarding the observation, it was carried out with some of the students to verifyand assist the interview. This information was collated according to the theoretical framework on child labor, in merit of the ILO Convention No. 1. 138 and the Peruvian State on the minimum age for admission to employment. The results show that boys and girls are 100% part of the parents' work in the farm, caring for animals and housework.